2019
DOI: 10.3329/bmj.v46i2.40215
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological Evaluation of Patients with Meningitis in a Tertiary Care Hospital of Bangladesh

Abstract: Meningitis is a global health problem as mortality is high and a large proportion of survivors suffered from significant morbidity. The physicians are facing this challenge of emergency identification of this clinical syndrome, establishing its etiology and its prompt treatment not only to ensure survival but also to prevent long term sequelae in these patients. Poor outcomes caused by bacterial meningitis due to delays in diagnosis and treatment. In Bangladesh, the epidemiological study regarding meningitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…21,24 We had a higher proportion of female patients (Female = 57%, Male = 43%) in our study, which is contradictory with other studies like Bhat et al 25 , where patients of children were studied. In another Bangladeshi studies of meningitis which consist of 50 patients found male 62% and female 38%, 26 which is disimillar with our study might be due to the fact that less number of patients were included in their study. The Classical triad of meningitis or even the presence of two of the four common symptoms were observed to a lesser extent in our study when compared to the study conducted by Van de Beek et al 27 .…”
Section: Discussioncontrasting
confidence: 79%
“…21,24 We had a higher proportion of female patients (Female = 57%, Male = 43%) in our study, which is contradictory with other studies like Bhat et al 25 , where patients of children were studied. In another Bangladeshi studies of meningitis which consist of 50 patients found male 62% and female 38%, 26 which is disimillar with our study might be due to the fact that less number of patients were included in their study. The Classical triad of meningitis or even the presence of two of the four common symptoms were observed to a lesser extent in our study when compared to the study conducted by Van de Beek et al 27 .…”
Section: Discussioncontrasting
confidence: 79%